Pendidikan Tinggi Agama Islam dan Kohesi Sosial di Indonesia - Kosasih, Ojang; T, Sutaryat; Hanafiah, Hanafiah (Lembaga Yasin AlSys, 2023)
After the fall of authoritarian rule, religious people in Indonesia sought to improve relations through progressive Islamic education. Experts in this field study how community Islamic education leaders work to